Microfluidic Devices for Manufacture of Therapeutic Extracellular Vesicles: Advances and Opportunities - Amin Hassanzadeh‐Barforoushi; Xenia Sango; Ella L. Johnston; David Haylock; Yuling Wang (Journal of Extracellular Vesicles, 2025)
ABSTRACT Extracellular vesicles (EVs) are emerging as promising candidates in therapeutic applications due to their unique ability to mediate intercellular communication and deliver biological cargo. With increasing interest in EV‐based therapies, the development of scalable, cost‐effective and regulatory‐compliant production methods is critical. Microfluidic platforms offer transformative potential in EV manufacturing, providing precise control over production conditions, enhanced purity and seamless integration with quality control systems. This review highlights the advantages of microfluidic technologies in EV production, including fine‐tuning of shear stress to optimise yield, advanced purification strategies that achieve high recovery and purity, and on‐chip capabilities for EV loading and surface modification. Key challenges such as scaling up production while maintaining sterility, controlling EV release after immunoaffinity capture, and addressing clogging and fouling in microfluidic devices are discussed alongside emerging solutions. Additionally, the integration of AI‐driven automation and real‐time monitoring, as well as personalised EV manufacturing, is explored as pivotal innovations. Future directions emphasise the potential of combining size‐ and affinity‐based methods for EV isolation and aligning microfluidic technologies with regulatory requirements to accelerate clinical translation. Therefore, we believe microfluidics platforms for EV isolation hold immense potential to redefine EV manufacturing by enabling scalable, reproducible and high‐quality production systems essential for therapeutic applications.